The Relationship between Self-Compassion and Self-Efficacy with Academic Resilience among Students at Universitas Islam Negeri Walisongo Semarang - Refangga Rayyan Altrisan; Nikmah Rochmawati; Nadya Ariyani Hasanah Nurriyatiningrum (Tinta Emas Institute, 2024)
Students commonly encounter various challenges and difficulties during their college years, necessitating academic resilience. As a result, academic resilience becomes a crucial quality for every student to possess. This study aims to explore the relationship between self-compassion and self-efficacy with academic resilience among students at Walisongo State Islamic University, Semarang. The research population consisted of 14,498 students, and a sample of 100 students was selected using the incidental sampling technique. The study employs a quantitative correlational research method, utilizing three measurement instruments: academic resilience, self-compassion, and self-efficacy. The data analysis method used is multiple correlation testing. The research findings reveal that: 1) There is a positive correlation between self-compassion and academic resilience among students at Walisongo State Islamic University; 2) There is a positive correlation between self-efficacy and academic resilience among students at Walisongo State Islamic University; and 3) There is a positive correlation between self-compassion and self-efficacy with academic resilience among students at Walisongo State Islamic University. The higher the level of self-compassion in students, the greater their academic resilience. Likewise, the higher the level of self-efficacy in students, the greater their academic resilience. Therefore, it is crucial for students to cultivate both self-compassion and self-efficacy to enhance their academic resilience. The results of this study are valuable for improving students' self-compassion and self-efficacy, providing a basis for establishing counseling services at universities, and offering insights for future research to explore other variables related to academic resilience.